Utility of Perioperative Lung Ultrasound in Pediatric Cardiac Surgery: A Randomized Controlled Trial. (April 2018) - Song, In-Kyung; Kim, Eun-Hee; Lee, Ji-Hyun; Kang, Pyoyoon; Kim, Hee-Soo; Kim, Jin-Tae
Abstract : Background: Pediatric cardiac patients are at risk for perioperative respiratory insufficiency. The objective of this study was to assess the utility of perioperative lung ultrasound examination in pediatric cardiac surgery. Methods: In this randomized, controlled trial, children (5 yr old or younger) undergoing cardiac surgery were allocated into a control (n = 61) or intervention (n = 61) group. The control group received only lung ultrasound examinations at the end of surgery and 6 to 12 h after surgery. The intervention group received lung ultrasound examinations and an ultrasound-guided recruitment maneuver depending on ultrasound findings after inducing anesthesia, at the end of surgery, and 6 to 12 h after surgery. Primary outcomes were incidences of intra- and postoperative desaturation, and postoperative pulmonary complications. Multiple comparisons were corrected ( P ⩽ 0.017) in the primary outcome analysis. Results: Of the 120 children included in the analysis, postoperative desaturation (64% vs . 27%; P < 0.001; odds ratio [OR], 0.210; 95% CI, 0.097 to 0.456) occurred more in the control group. The incidences of intraoperative desaturation (36% vs . 19%; P = 0.033; OR, 0.406; 95% CI, 0.176 to 0.939) and postoperative pulmonary complications (12% vs. 3%; P = 0.093; OR, 0.271; 95% CI, 0.054 to 1.361) were similar between the groups. Lung ultrasound scores were better in the intervention group than in the control group. Duration of mechanical ventilation was longer in the control group than in the intervention group (38 ± 43 vs . 26 ± 25 h; 95% CI of mean difference, 0 to 25; P = 0.048). Conclusions: Perioperative lung ultrasound examination followed by ultrasound-guided recruitment maneuver helped decrease postoperative desaturation events and shorten the duration of mechanical ventilation in pediatric cardiac patients. Visual Abstract: An online visual overview is available for this article athttp://links.lww.com/ALN/B682 . Abstract : Using lung ultrasound to optimize lung recruitment improves clinical outcomes in children having cardiac surgery.